2011
DOI: 10.1590/s1516-635x2011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella fecal excretion control in broiler chickens by organic acids and essential oils blend feed added

Abstract: Salmonellosis is an important disease with economic impact as it may affect animal performance and may result in foodborne disease in humans through the eggs and carcass contamination. Regarding the Salmonella control, it is possible to decrease its fecal excretion and the contamination of chicken carcasses by adding organic acids to the feed or drinking water at appropriate times. The aim of this study was to test a blend of organic acids and essential oils in broilers challenged with Salmonella Enteritidis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…There are many plant essential oils and other products from plants that can be used to control bacteria, including Salmonella (Bajpai et al, 2012). Essential oils added to feed or water have been used to control fecal excretion of Salmonella, with promising results (Borsoi et al, 2011). The authors just cited, used live animals for their trials.…”
Section: Discussionmentioning
confidence: 99%
“…There are many plant essential oils and other products from plants that can be used to control bacteria, including Salmonella (Bajpai et al, 2012). Essential oils added to feed or water have been used to control fecal excretion of Salmonella, with promising results (Borsoi et al, 2011). The authors just cited, used live animals for their trials.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Salmonella challenge can cause higher Salmonella colonization in cecal or fecal contents ( Bohez et al , 2008 ; Borsoi et al , 2011 ) but decrease Lactobacillus colonies ( Audisio et al , 2000 ). In agreement with these results, our study also revealed that Salmonella colonies were increased in the small and large intestines of Salmonella -challenged broilers whereas the Lactobacillus population was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Organic acid with other additive type Feed 9 (Abudabos et al, 2014;Borsoi et al, 2011;Cerisuelo et al, 2014;Gao et al, 2019;Grilli et al, 2011;Hassan et al, 2010;Machado et al, 2014;Natsir et al, 2017;Pathak et al, 2017) 0 Amaril (Pathak et al, 2017), Gallimix (Abudabos et al, 2014), FormaXOL (Abudabos et al, 2014, Biacid™ (Hassan et al, 2010), Novacid (Manafi et al, 2019), Acid Pak 4-Way R (Lilly et al, 2011), Activate R Water 6 Harris et al, 2019;Lilly et al, 2011;Machado et al, 2014;Michel et al, 2019;Willis et al, 2009 Gracia, Millan, et al, 2016;Molatova et al, 2011;van Gerwe et al, 2010;Zeiger et al, 2017) 2 (Hermans et al, 2010; Lodestar C8-C10 (van Gerwe et al, 2010), Fortibac R Water 1 (Hermans et al, 2012) 1 (Metcalf et al, 2011) Organic acid with other additive type Feed 4 (Grilli et al, 2013;Guyard-Nicodeme et al, 2016;Sima et al, 2018;Thibodeau et al, 2015) 3 (Gracia, Millan, et al, 2016;Ocejo et al, 2017;Thibodeau et al, 2014) Power van Bunnik et al, 2012) 1 (Gracia, Millan, et al, 2016) Combinations of different types ...…”
Section: No Effect or Inconclusive Commercial Productsmentioning
confidence: 99%